(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Kolesnichenko N. Yu. The concept of modernization of professional training of bachelors of Romance-Germanic Philology based on competence approach. The article is focused on the problems of improving the professional training of bachelors of Romance-Germanic Philology. Particular attention is paid to the design of a conceptual model of modernization professional training of bachelors of Romance-Germanic Philology with competence-based approach being its ground. Main phases, general didactic and specific principles necessary for the organization of this process are highlighted.